TMOD-38. GMYC: A NOVEL INDUCIBLE TRANSGENIC MODEL OF GROUP 3 MEDULLOBLASTOMA. (5th November 2018) - Rosén, Gabriela; Weishaupt, Holger; Mainwaring, Oliver; Swartling, Fredrik
Abstract: Group 3 medulloblastoma (MB) carry the worst prognosis of all MB. The transcription factors MYC and MYCN have been suggested drivers for a subset of these tumors, with MYC amplifications (17–20%) representing the most common genetic alteration in Group 3 tumors, while MYCN amplifications (4–6%) are less frequent. To improve current treatment options for these patients, it is of crucial importance to decipher differential features of MYCN - and MYC -driven MB and to establish accurate animal models for these patients. By driving MYC from the hindbrain-specific Glutamate transporter 1 ( Glt1 ) promoter using a Tet-OFF system we established a novel murine model of MYC -driven MB (GMYC), which accurately recapitulates aggressive Group 3 MB. GMYC tumors develop without any p53 mutations and with 70% penetrance. Tumor-prone GMYC mice can further be cured by MYC -depletion through dox treatment. Comparison of transcriptional profiles between GMYC and our MYCN -driven GTML tumors revealed that both models accurately represent Group 3 MB, while showing differential expression of key features of MYC - or MYCN -driven tumors. CDKN2A was identified as one of the top upregulated genes in our GTML model as compared to our GMYC model. CDKN2A encodes two tumor suppressors, p16INK4A and p14ARF, which are key regulators of cell cycle progression and activation of p53. Similar enhancement of CDKN2A was observed in MYCN -amplified as compared to MYC -amplified Group 3/4 patients. Tumor formation following partial or complete knockout of CDKN2A significantly increased tumor penetrance in GTML as compared to GMYC animals. Similarly, CDKN2A levels significantly correlate with poor prognosis in MYCN amplified MB patients while as compared to MYC amplified patients were CDKN2A levels are low. This suggests that MYC is regulating and suppressing CDKN2A during MB formation and further advocates that pharmacological restoration of CDKN2A would be a potential future therapy for this group of high-risk MB patients.